Analysis of diaphragm behaviour in composite multi girder railway bridges - Sieffert, Yannick; Michel, Gérard; Martin, Didier; Keller, David; Jullien, Jean‐François (Journal of Civil Engineering and Management, 2004)
This study focuses on mechanical behaviour of diaphragm in composite multigirders railway bridge. The aim is to predict and to compare, with a numerical simulation, the transverse and longitudinal distribution of traffic loads in different girders and in the slab for the cases with and without intermediary diaphragm. A 3‐D finite element model is developed to represent the actual geometry of multigirder bridge. Durability of the concrete bridge deck is directly related to cracking, so a non‐linear constitutive equation is used for the concrete deck. This study focuses on the response of a bridge with and without dipahragm under a UIC and TGV loading. To achieve this aim, a static failure analysis is performed. Our analysis concluded that diaphragm is not necessary, so it seems to be possible to remove the diaphragms. First Published Online: 14 Oct 2010